Implementasi Metode Demonstrasi dalam Membantu Pemahaman Kitab Sullamut Taufiq Santriwati Mukim di Pondok Pesantren Putri 1 Al-Amien Prenduan Sumenep Madura - Faiqotun Nisa; Muhammad Firdaus (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The demonstration method is a learning method using teaching aids or direct practice to clarify an understanding of learning to students. Al Amien Prenduan Girls' Islamic Boarding School 1 is one of the Islamic boarding schools that applies learning using the demonstration method through the book Sullamut Taufiq in certain chapters. In this method, the researcher found that the female students at the Al-Amien Prenduan Girls' Islamic Boarding School 1 had applied the demonstration method. so that most of the female students living at the Al-Amien Prenduan Girls' Islamic Boarding School 1 better understand learning when using the demonstration method. Therefore, researchers are interested in finding out more about the implementation of the demonstration method to improve understanding of the book Sullamut Taufiq in certain chapters. This research focuses on: 1) how to implement the demonstration method in increasing understanding of the book Sullamut Taufiq at the Al-Amien Prenduan Girls' Islamic Boarding School 1. 2). What are the supporting and inhibiting factors for using the demonstration method in increasing understanding of the book Sullamut Taufiq at the Al-amien Prenduan 1st Girls' Islamic Boarding School. This research uses qualitative fieldwork with a case study type, data collection techniques using interviews, observation and documentation. The informants in this research were caregivers, teachers, consultants and students at the Islamic Boarding School for Girls 1 Al-Amen Prenduan. The results of the research show that the implementation of the demonstration method in increasing understanding of the book Sullamut Taufiq at the Al-Amien Prenduan Islamic boarding school focuses on the application of the method in learning. because, in order to improve good learning outcomes, first improve good and effective understanding by using appropriate learning methods. Such as using the demonstration method in understanding the book Sullamut Taufiq. Although there are problems faced by teachers, such as a lack of student enthusiasm and not all material can be demonstrated.